2020
DOI: 10.1080/15384101.2019.1710912
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Litchi Seed Aqueous Extracts play a role in suppression of epithelial-mesenchymal transition, invasion and migration in breast cancer cells

Abstract: We carried out this study to unravel the function of Litchi Seed Aqueous Extracts (LSAE) on biological functions of breast cancer (BC) cells. MTT assay was adopted to measure proliferation of BC cells (MCF7, BT474 and MDA-MB-231) and normal mammary cells (MCF10A) under different time points (24, 48 and 72 h) and different concentrations (50, 100, 200 and 400 μg/mL). MCF-7 cells were selected for subsequent experiments and were grouped into blank group, negative control (NC) group, low-, medium-and high-dose LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Elevated ER and PR levels enhance mammary epithelial cell sensitivity to estrogen, which can trigger mammary gland hyperplasia. When the ER signaling pathway becomes dysregulated, intracellular protein function may be altered, leading to an imbalance in gene expression and resulting in mammary gland cell hyperproliferation or apoptosis arrest [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated ER and PR levels enhance mammary epithelial cell sensitivity to estrogen, which can trigger mammary gland hyperplasia. When the ER signaling pathway becomes dysregulated, intracellular protein function may be altered, leading to an imbalance in gene expression and resulting in mammary gland cell hyperproliferation or apoptosis arrest [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study (46,47). a number of studies have used the two aforementioned cell lines to study the migration and invasion of breast cancer cells; therefore, the two cell lines were selected for the present study (48)(49)(50). Yang et al (51) demonstrated that aPS inhibited the proliferation of hepatocellular carcinoma cells partly via immunomodulation.…”
Section: Discussionmentioning
confidence: 99%
“…Lychee seedt is rich in starch and nutrients, which can be used as medicinal materials. As a traditional Chinese medicinal material, Lychee seed is warm, sweet and slightly bitter, it has the effects of qi clearing, cold removing and pain relieving, etc [3][4] . Lychee seed exhibits an pivotal role in the development of health care products and pharmaceutical research, however its research in the field of cosmetics is not extensive, so this article mainly introduces the role of lychee seed fermentation liquid in anti-inflammatory, antioxidant and safety.…”
Section: Introductionmentioning
confidence: 99%